Diagnóstico de la salud y seguridad ocupacional en la Asociación Agropecuaria “Pupana Sur”, parroquia Guaytacama, cantón Latacunga, provincia de Cotopaxi 2021 - Merizalde Suárez, Jonathan Alexander (2021)
This research was carried out in the Asociación Agropecuaria "Pupana Sur", in the parish of Guaytacama with emphasis on the diagnosis of occupational health and safety (OSH) applied to the members of the association, the main objective was to diagnose the incidence of occupational hazards in the health of the members of the Asociación Agropecuaria "Pupana Sur" Parroquia Guaytacama, Canton Latacunga, Province of Cotopaxi 2021, for which a survey was applied based on socio-economic and risk indicators that allowed to characterize the farmer and his health problems, in addition indicators were established on COVID 19; The results obtained show that 53.3% of the members are constantly exposed to physical risk factors such as heat, cold, sun rays, sunburn, sun exposure, and other health problems: heat, cold, sun rays, in the same way 100% of the members of the association are persistently exposed to biological factor such as: mosquito bites, among other indicators evaluated, in safety risks 86.7% presented accidents and affections in their workplace, such as: cuts, blows, etc. This has had musculoskeletal consequences. The indicators COVID-19 are currently going through exposure to indicator 13.3% of the partners are into a high risk of contagion, we obtained 40% of the partners have already gone through this disease.